Problematisierung statt Optimierung? : Verhandlungen einer klärungsbedürftigen Beziehung in der Erwachsenenbildung - Ebner von Eschenbach, Malte Dr; Kondratjuk, Maria Jun.Prof. Dr; Stimm, Maria Dr; Trumann, Jana Dr; Wagner, Farina (Debatte Sonderheft., 2022)
The first special issue of the journal Debate brings together contributions and replicas on adult education that put a change of perspective up for discussion: While optimization is often used as a solution to educational problems, the special issue focuses on problematization. Optimization implicitly presupposes a goal that has already been defined, while problematization allows for openness towards its object. The associated implications are developed along the following empirical fields: migration research, higher education, scientific communication and continuing education advice.